Efektivitas Penerapan Akuntansi Pertanggungjawaban Untuk Pengendalian Biaya Pada Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Jawa Timur - Kusnan; Sunarya, Aris (Soetomo Magister Ilmu Administrasi, 2025)
Management of regional finances and assets is important to support public services and improve community welfare. The Regional Financial and Asset Management Agency (BPKAD) of East Java Province has a key role in this matter. One of the obstacles faced by BPKAD is budgeting and reporting errors, as well as a lack of effective control over costs. Therefore, an accounting system is needed that can support better cost control. This research aims to analyze the effectiveness of implementing responsibility accounting and its role in controlling costs at BPKAD East Java Province. The research method used is qualitative with a case study approach. Data sources were obtained from interviews, documentation and observation. The research results show that responsibility accounting has been implemented but is not yet optimal. Responsibility accounting plays a role in detecting these problems, although it needs improvement. Lack of human resources is the main obstacle. For this reason, it is necessary to improve the quality of human resources and engineer the budgeting and reporting processes to increase the effectiveness of cost control at BPKAD East Java Province.